2021
DOI: 10.15244/pjoes/125768
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Differences in Growth and Physiological Characteristics of <i>Populus cathayana</i> under Pb Stress and <i>Leucoagaricus</i> sp. Colonization

Abstract: Populus cathayana was used as a model species to investigate sexual differences in plant growth and physiological responses to lead (Pb) stress (0, 150 and 300 mg Pb 2+ kg-1 dry soil) with mycorrhizal (Myc) fungi colonization by Leucoagaricus sp. Results showed that high concentration of Pb stress (300 mg/ kg) caused disorder in photosynthesis, inhibited plant biomass, changed antioxidant enzyme activities and increased Malondialdehyde (MDA) content in both sexes, particularly in females. Male saplings showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…It has been found that after inoculation with AM the Pro of male P. cathayana increased under drought and salt stress ( Li et al., 2015 ), while the Pro accumulation of female was significantly increased only after inoculation with AM under salt stress and Pb stress ( Wu et al., 2016 ), and the Pro of male was significantly higher than that of female after inoculation with AM under Pb stress ( Feng et al., 2021 ). In the present study, females and males can produce more Pro to regulate osmotic pressure under Pb stress, while Pb + AM treatment significantly increased the Pro accumulation of males ( Figure 3D ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that after inoculation with AM the Pro of male P. cathayana increased under drought and salt stress ( Li et al., 2015 ), while the Pro accumulation of female was significantly increased only after inoculation with AM under salt stress and Pb stress ( Wu et al., 2016 ), and the Pro of male was significantly higher than that of female after inoculation with AM under Pb stress ( Feng et al., 2021 ). In the present study, females and males can produce more Pro to regulate osmotic pressure under Pb stress, while Pb + AM treatment significantly increased the Pro accumulation of males ( Figure 3D ).…”
Section: Discussionmentioning
confidence: 99%